Initial experience with Edwards SAPIEN valve transcatheter implantation in native RVOT in Latvia - Auzina, Luize; Lubaua, Inguna; Ligere, Elina; Lace, Inga; Bergmane, Inta; Matsone-Matsate, Baiba; Silis, Pauls; Smits, Lauris; Sikora, Normunds; Søndergaard, Lars; Ozolins, Valts (Acta medica Lituanica, 2020)
Transcatheter pulmonary valve implantation has been a well-known method for more than a decade, but there are still many challenging cases when a personalized solution is needed. We report a case of a 15-year-old female patient with tetralogy of Fallot, who underwent a surgical correction during infancy. Because of progressive pulmonary regurgitation, stenosis, and right ventricle dilatation, transcatheter pulmonary valve implantation in the native right ventricle outflow tract (RVOT) using Edwards SAPIEN valve was performed. A “landing zone” was created prior to the intervention of stenting the RVOT and the right pulmonary artery. The transcatheter approach for pulmonary valve replacement in a native RVOT is a reasonable alternative to the surgical approach.
Keywords: Edwards SAPIEN valve; transcatheter pulmonary valve implantation; Tetralogy of Fallot; native RVOT